Cox Extended Regression Method in Survival Analysis; Case Study of Diarrhea Patients - Syafitri, Ina Nur; Rahmawati, Rahmawati; Qadrini, Laila (Journal of Mathematics and Applied Statistics, 2023)
The study aims to implement survival analysis at the healing rate of a diarrhea patient using the cox extended regression method and estimate the parameters of the cox extended regression model with variables that affect diarrhoea. The data on this study USES the data of diarrhea patients at the PKM Sendana of Majene Regency 2022. Analysis of variable body temperature and vomiting variables does not meeththe assumption of proportiontional hazard, this indicates that variable body temperature and puke variables are time-consuming. The best model of the regression cox extended model is a model based onhthe akaike informationccriterion value (AIC) of 500.4363. The factors of body temperature and vomiting, where patients who haven't had a change in body temperature have a probability of healing 2.27 times faster than those who have a temperature change. Whereas diarrhea patients who do not experience vomiting during treatment have a probability of recovery of 2.72 times faster than those who experience vomiting during the treatment.